Urinary catheterization 1: indications. (2nd September 2019) - Tan, Elizabeth; Ahluwalia, Aashish; Kankam, Hadyn; Menezes, Pravin
Abstract : Urinary catheterization is an important procedure that is regularly performed in hospital. All clinicians should have a good working knowledge of urinary catheters and the competence to manage them effectively. This topic will be discussed over two articles: this first article will focus on indications, and the second on techniques and managing failure. There are multiple indications for urethral catheter insertion and a range of catheter types and sizes. The choice of catheter is dependent on the patient and indication. This article discusses this in more detail to help guide clinicians involved in urethral catheterization.